Increased bronchial parasympathetic tone in elite cross-country and biathlon skiers: a randomised crossover study - Stang, J.; Couto, M.; Carlsen, K.-H.; Stensrud, T. (British Journal of Sports Medicine, 2015)
Background: Increased parasympathetic activity in endurance-trained athletes has been reported by heart rate variability and pupillometry. Our primary objective was to assess parasympathetic activity and tone in the lower respiratory tract by investigating the effect of cholinergic antagonism by inhaled ipratropium bromide compared to the ß2-receptor stimulating effect of inhaled salbutamol in elite cross-country and biathlon skiers. We also examined the medications` relationship to cholinergic sensitivity as measured by bronchial responsiveness to methacholine (PD20met).